Identification and purification of a human immunoglobulin-enhancer-binding protein (NF-kappa B) that activates transcription from a human immunodeficiency virus type 1 promoter in vitro. - Kawakami, K (1988)
The enhancer-binding factor NF-kappa B, which is found only in cells that transcribe immunoglobulin light chain genes, has been purified from nuclear extracts of Namalwa cells (human Burkitt lymphoma cells) by sequence-specific DNA affinity chromatography. The purified NF-kappa B has been identified as a 51-kDa polypeptide by UV-crosslinking analysis. "Footprint" and methylation-interference analyses have shown that purified NF-kappa B has a binding activity specific for the kappa light chain enhancer sequence. The purified factor activated in vitro transcription of the human immunodeficiency virus type I promoter by binding to an upstream NF-kappa B-binding site.